Prevalencia y fatores de riesgo de discapacidaden adultos mayores atendidos en el S.C.S. Las Cañas canton Santa Rosa, año 2013. - Andrade Peláez, María Belén (2016)
This work can prove that disability apart from being a disease, it is associated with several factors such as economic, social and physical, in the database health sub center Reeds found that there are 80 elderly patients with disabilities, of which only 56.25 for center are seen at 43.75 for center and fail to do it on their type disability, and economic factor, along with the distance to the nursing home is not allowed.